Strategy to Reduce Nurse Turnover Intention at X Hospital, Depok City - Audrey, Audrey Dhea Azzahra; Asropi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
This study aims to identify factors that influence nurse turnover and formulate strategies to reduce it at Hospital X, Depok City. Turnover intention is defined as an employee's desire to find a better job than before, which requires the agency's attention in understanding the reasons behind an employee's decision to leave their job. Hospital X, Depok City was recorded to have a high turnover rate in 2022, which was 12% compared to the previous year. This study uses a qualitative method with a descriptive approach, where data is collected through interviews and documentation, then analyzed using triangulation techniques through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the main factors influencing turnover intention are workload, job satisfaction, and salary satisfaction. The proposed strategies include implementing performance evaluations, increasing work comfort, and increasing the number of necessary medical devices.This study makes significant contributions to the theory and practice of hospital management, particularly in understanding and addressing the factors that influence nurse turnover. By identifying the effects of workload, job satisfaction, and salary satisfaction on turnover intention, this study broadens the horizons in human resource management in the healthcare sector. In addition, the recommendations provided are not only relevant to Hospital X, but also have broad policy implications for other healthcare institutions. The proposed strategies, such as structured performance evaluation and improving employee welfare, can be adapted by other hospitals to reduce turnover and increase nurse retention. Thus, the results of this study contribute to creating a more stable and productive work environment, which ultimately supports improving the quality of healthcare services in various institutions.